1989
DOI: 10.1149/1.2097378
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Epitaxial Silicon from Silane at Low Temperatures: I . Very Low Pressure Deposition

Abstract: The deposition of epitaxial silicon films at temperatures from 600°–800°C by both very low‐pressure chemical vapor deposition (VLPCVD) and plasma‐enhanced chemical vapor deposition (PECVD) has been examined. The VLPCVD deposition process is first order in silane partial pressure, zero order in hydrogen partial pressure, and exhibits a low, 8–12 kcal/ mole, activation energy for temperatures from 700°–800°C with 1–15 mtorr silane and hydrogen. For temperatures below 700°C an activation energy of 40 kcal/mole is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…[1][2][3][4][5] In our recent study of CVD Si at 600-750°C and 20-80 Torr in a lamp-heated single-wafer reactor, 5 the apparent activation energy for epi-Si is 2.1 eV and that for poly-Si 1.6 eV, in agreement with earlier published results. 1,3,6 Under these deposition conditions, first-order reaction kinetics was found for the ͑average͒ growth rate of epi-Si as well as for poly-Si with respect to the partial pressures of SiH 4 .…”
supporting
confidence: 85%
“…[1][2][3][4][5] In our recent study of CVD Si at 600-750°C and 20-80 Torr in a lamp-heated single-wafer reactor, 5 the apparent activation energy for epi-Si is 2.1 eV and that for poly-Si 1.6 eV, in agreement with earlier published results. 1,3,6 Under these deposition conditions, first-order reaction kinetics was found for the ͑average͒ growth rate of epi-Si as well as for poly-Si with respect to the partial pressures of SiH 4 .…”
supporting
confidence: 85%
“…͑6͔͒ proceeds faster at high temperature. 40 In the low-pressure region (ϳ1 Torr and below͒ it has been reported that the Si growth rate is independent of the hydrogen partial pressure, 11,29,39,43 this behavior could also be described by Eq. ͑11͒.…”
Section: ͑10͒mentioning
confidence: 96%
“…1-5, the deposition kinetics for Si growth is studied. Several publications were found in the literature about the deposition kinetics of epitaxial 15,28-33 and polycrystalline 28,29,31,32,[34][35][36][37][38][39][40] Si film growth from silane performed at deposition pressure ranging from ultrahigh vacuum ͑UHV͒ to atmospheric pressure. Two reaction paths describing the Si growth are homogeneous and heterogeneous decomposition of silane and Si hydrides.…”
Section: Growth Kineticsmentioning
confidence: 99%
“…1 A low growth temperature ͑400-700°C͒ prevents the deleterious effects of autodoping from the substrate and lateral diffusion from contacts. To achieve such a low temperature growth, various techniques, such as ultrahigh vacuum chemical vapor deposition ͑UHV-CVD͒, 1,2 very low pressure CVD, 3 plasma enhanced CVD, 4 and low pressure UHV electron-cyclotron-resonance ͑ECR͒ CVD [5][6][7][8] have been used. The advantages of ECR-CVD are the low particulate production in the reactor, enhanced growth rate at low temperatures, and the ability to control plasma potentials, and hence ion bombardment of the substrate, during growth.…”
mentioning
confidence: 99%